The economics of Europe : what the Common Market means for Britain - Pinder, John; Federal Trust for Education and Research (London : C. Knight for the Federal Trust, 1971)
The idea of this book arose from a conference organized by the Federal Trust at Wiston House on 7 - 9 May 1971, at which a number of the authors presented papers that have been developed into the chapters of this book
[Based on papers given at] a conference organised by the Federal Trust at Wiston House on 7-9 May, 1971.
Includes bibliographical references.
osc 14/11/2018
Loans